Memahami Komunikasi Sosial: Front Stage dan Back Stage Menurut Teori Dramaturgi Goffman - Khofifah Indar Parawansah (Al-Qolamuna: Journal Komunikasi dan Penyiaran Islam, 2026)
Erving Goffman's dramaturgical theory offers an important perspective in understanding social communication as a performance process involving impression management. This study aims to analyze how the concepts of front stage and back stage are applied in individuals' social communication in everyday life. The approach used is qualitative, using literature studies and observations of social interaction patterns in modern social contexts. The front stage is understood as a public interaction space where individuals display behaviors that have been adjusted to norms, social roles, and audience expectations. Meanwhile, the back stage is a private space that allows individuals to express themselves more freely without social pressure and serves as a preparation area before performing in public. The results show that individuals consistently separate behavior and communication methods between the front stage and back stage. On the front stage, communication tends to be formal, controlled, and oriented toward a positive self-image. In contrast, on the back stage, communication is more spontaneous, honest, and reflects a true personal identity. This study also found that in the context of social media, the boundaries between the front stage and back stage are increasingly blurred, as private spaces are often presented for public consumption. This encourages individuals to continue practicing impression management even outside of face-to-face interactions. In conclusion, Goffman's dramaturgical theory is relevant in explaining the dynamics of contemporary social communication. Understanding the front stage and back stage helps explain how individuals form social identities, maintain relationships, and adapt to the demands of an ever-evolving social environment. Abstrak Teori dramaturgi Erving Goffman menawarkan perspektif penting dalam memahami komunikasi sosial sebagai suatu proses pertunjukan yang melibatkan pengelolaan kesan (impression management). Penelitian ini bertujuan untuk menganalisis bagaimana konsep front stage dan back stage diterapkan dalam komunikasi sosial individu pada kehidupan sehari-hari. Pendekatan yang digunakan adalah kualitatif dengan metode studi literatur dan observasi terhadap pola interaksi sosial dalam konteks sosial modern. Front stage dipahami sebagai ruang interaksi publik di mana individu menampilkan perilaku yang telah disesuaikan dengan norma, peran sosial, dan ekspektasi audiens. Sementara itu, back stage merupakan ruang privat yang memungkinkan individu mengekspresikan diri secara lebih bebas tanpa tekanan sosial, serta menjadi tempat persiapan sebelum tampil di ruang publik. Hasil penelitian menunjukkan bahwa individu secara konsisten memisahkan perilaku dan cara berkomunikasi antara front stage dan back stage. Pada front stage, komunikasi cenderung formal, terkontrol, dan berorientasi pada citra diri positif. Sebaliknya, pada back stage, komunikasi bersifat lebih spontan, jujur, dan mencerminkan identitas personal yang sesungguhnya. Penelitian ini juga menemukan bahwa dalam konteks media sosial, batas antara front stage dan back stage semakin kabur, karena ruang privat sering kali dipresentasikan sebagai konsumsi publik. Hal ini mendorong individu untuk terus melakukan pengelolaan kesan bahkan di luar interaksi tatap muka. Kesimpulannya, teori dramaturgi Goffman relevan dalam menjelaskan dinamika komunikasi sosial kontemporer. Pemahaman terhadap front stage dan back stage membantu menjelaskan bagaimana individu membentuk identitas sosial, menjaga hubungan, serta menyesuaikan diri dengan tuntutan lingkungan sosial yang terus berkembang.